Corporate strategy (remastered) 1 : high performance strategy and leadership in a volatile, disrupted world - Hunter, Paul Wilson, 1954- (New York, NY : Routledge, 2020)
'Since 2000, more than half of the Fortune 500 companies have either gone bankrupt, been acquired, or are experiencing stagnation or decline as a result of extreme digital and social disruption. In recognition of this dilemma, Corporate Strategy (Remastered) will assist even the most experienced strategy practitioner tackle disruption and all aspects of change head on. This is the first book in the series, it provides a prescriptive solution to the way all approaches to strategy should be practiced in the future; in a context we refer to as Third Wave Strategy and its construct; a fully integrated, strategic management framework. The second is a fieldbook, it describes the methods and means to ensure successful implementation. An illustration of Third Wave Strategy in practice is reflected in a description of strategy deployed by the highly successful Amazon corporation. Many of the components of strategy that are included in the framework will already be familiar to the reader, others are very new. Each of the individual components discussed are supported by examples drawn from real life case studies. The overall value of the book is that it represents a fresh, holistic, dynamic and systemic approach to strategy in a format that, frankly, hasn't existed before. In this book readers are also introduced to many of the soft/human elements of strategy - the primary components that make it work. Examples of topics addressed include open strategy; communities of strategy practice; reframing; sponsive strategic thinking; systemic, cognitive strategy practice, organisational learning, strategic business intelligence'--
Includes bibliographical references and index.
Keywords: Strategic planning; Leadership